A Triage Approach to Managing a Two Year Wait-List in a Chronic Pain Program - Alexander J Clark; Ian Beauprie; Lynne B Clark; Mary E Lynch (Pain Research and Management)
OBJECTIVE: Individuals with chronic pain referred to specialist chronic pain management programs frequently wait months to years for assessment and care. In the authors' pain management program, approximately 600 patients are on the waiting list. An innovative recommendation program to encourage and educate referring physicians to continue active care of pain during this waiting period was developed.